2021
DOI: 10.1111/cas.15041
|View full text |Cite
|
Sign up to set email alerts
|

The BAFF/NFκB axis is crucial to interactions between sorafenib‐resistant HCC cells and cancer‐associated fibroblasts

Abstract: The tumor microenvironment affects malignancy in hepatocellular carcinoma (HCC) cells, and cancer‐associated fibroblasts (CAFs) play an important role in the microenvironment. As recent studies indicated a difference between CAFs isolated from chemoresistant and non‐resistant cancer tissues, therefore we investigated the intracellular mechanism in resistant HCC co‐cultured CAFs and interactions between these CAFs with cancer cells. We established a sorafenib‐resistant (SR) Huh7 (human HCC) cell line, and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Given the central role of sorafenib in HCC therapy, it is urgent to further study the exact mechanisms of sorafenib resistance in HCC so as to improve chemosensitivity of HCC to sorafenib. Recent studies have revealed that the activation of NF-kB is identified as a crucial molecule leading to sorafenib resistance in HCC (102)(103)(104). Meanwhile, ncRNAs have been considered to be vital regulators in sorafenib resistance of HCC (105).…”
Section: Nf-kb-associated Chemoresistance In Hcc and Ncrnas-targeting Therapymentioning
confidence: 99%
“…Given the central role of sorafenib in HCC therapy, it is urgent to further study the exact mechanisms of sorafenib resistance in HCC so as to improve chemosensitivity of HCC to sorafenib. Recent studies have revealed that the activation of NF-kB is identified as a crucial molecule leading to sorafenib resistance in HCC (102)(103)(104). Meanwhile, ncRNAs have been considered to be vital regulators in sorafenib resistance of HCC (105).…”
Section: Nf-kb-associated Chemoresistance In Hcc and Ncrnas-targeting Therapymentioning
confidence: 99%
“…In HCC, CAFs were found to increase chemoresistance against sorafenib and cisplatin through the HGF-Met-ERK pathway [53,54]. Two other studies further confirmed that CAFs induce drug resistance against sorafenib, which in turn leads to an increase in liver cancer cell aggressiveness [55,56].…”
Section: Definition and Use Of Cafs For In Vitro Liver Cancer Studiesmentioning
confidence: 85%
“…Only eight studies so far (representing 14%) have investigated the effect of the tumour cells on the CAF population and of that two-thirds of the papers used the LX-2 cell line as CAF surrogate (Table 2). The presence of cancer cell lines can promote the CAF phenotype in LX-2 as shown by the induction of α-SMA, MMP-9, VEGF, and FGF [55,61,73,78]. This is likely mediated by secreted factors as the majority of the papers used CM transfer, exosome transfer, or transwell assays (Table 2).…”
Section: Models For Caf-tumour Interaction In Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoresistance serves as another significant mechanism mediating HCC progression and metastasis after radical surgery. A recent study found that co-culture with CAFs maintains sorafenib resistance in HCC cells through B-cell-activating factor (BAFF)/NF-κB-dependent pathway ( 42 ); otherwise, overexpressed immunosuppressive cell differentiation (CD)-73 in cancer cells induced by CAFs can facilitate the resistance of sorafenib and cisplatin in HCC patients ( 60 , 61 ).…”
Section: The Mechanisms For Cafs In Supporting Hcc Progressionmentioning
confidence: 99%